Facial Expressions in Context: Electrophysiological Correlates of the Emotional Congruency of Facial Expressions and Background Scenes - Xu, Qiang; Yang, Yaping; Tan, Qun; Zhang, Lin (Frontiers in Psychology, 2017)
Facial expressions can display personal emotions and indicate an individual’s intentions within a social situation. They are extremely important to the social interaction of individuals. Background scenes in which faces are perceived provide important contextual information for facial expression processing. The purpose of this study was to explore the time course of emotional congruency effects in processing faces and scenes simultaneously by recording event-related potentials (ERPs). The behavioral results found that the categorization of facial expression was faster and more accurate when the face was emotionally congruent than incongruent with the emotion displayed by the scene. In ERPs the late positive potential (LPP) amplitudes were modulated by the emotional congruency between faces and scenes. Specifically, happy faces elicited larger LPP amplitudes within positive than within negative scenes and fearful faces within negative scenes elicited larger LPP amplitudes than within positive scenes. The results did not find the scene effects on the P1 and N170 components. These findings indicate that emotional congruency effects could occur in late stages of facial expression processing, reflecting motivated attention allocation.